Nacionalna fantazija i kultura pamćenja američkih devedesetih u romanu _Leviathan_ Paula Austera - Šesnić, Jelena (Array, 2014)
National fantasy and the culture of memory in the American nineties: the case of Paul Auster’s novel Leviathan Several readers, such as Andreas Huyssen, have designated the nineteen-nineties as “a culture of amnesia, ” suffering from a deficit of history. On closer look, however, it turns out that the nineties were obliged to search for some alternative modes of conceptualizing the past that would revise and supplement the extant historiography. This revisionist tendency was due in particular to, what other critics of the period, such as Phillip Wegner, have termed “the Long Nineties” being a decade that evolves between the “two deaths.” Donald Pease, for his part, insists on the inexorable workings of a deeply embedded US national security state fantasy underlying not only the Cold War consensus but also monopolizing the US citizens' relationship with the nation-state. Once the Cold War ended, this version of American exceptionalism, a powerful national idea, had to be replaced with a new dispensation, which found its expression in the new covenants with America only to culminate in the Global War on Terror in the wake of 9/11. However, before this consolidation could take place, a moment of crisis opened up, such that is considered in Paul Auster’s 1992 novel Leviathan. Leviathan characteristically works with the processes of memory, both collective and individual, while showing how enmeshed they are with the questions of identity, individualism, society, politics, ethics, and art, as Auster’s characters-as-writers self-consciously probe the meaning of social covenant in late twentieth-century, post-Vietnam, and post-Cold War America. Several intersecting frames of analysis are considered in order to bring the notions of collective and individual memory processes to bear on the analysis of the period in question, particularly cultural psychoanalysis, memory studies and political theory.